2016
DOI: 10.1016/j.vaccine.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Development and approval of live attenuated influenza vaccines based on Russian master donor viruses: Process challenges and success stories

Abstract: HighlightsLAIV has been used in Russia for decades.Russian LAIV consistently provides superior effective protection against influenza.It was incorporated into the WHO global pandemic influenza action plan.A number of Russian LAIVs against pandemic influenza viruses have been prepared.Russian LAIV technology was transferred to a number of developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 21 publications
0
32
0
2
Order By: Relevance
“…LAIVs have been introduced firstly by Russia . They have been used in adults since the 1950s, and from 1987 onwards, the use of Russian LAIV for the prophylaxis of influenza has been widely extended to all age groups including children aged over 3 years . LAIVs have been licensed in the Unites States (US) in 2003 for healthy subjects aged 2‐49 years and in the European Union (EU) in 2012 for healthy children aged 2‐17 years .…”
Section: Iga Immune Response Upon Influenza Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…LAIVs have been introduced firstly by Russia . They have been used in adults since the 1950s, and from 1987 onwards, the use of Russian LAIV for the prophylaxis of influenza has been widely extended to all age groups including children aged over 3 years . LAIVs have been licensed in the Unites States (US) in 2003 for healthy subjects aged 2‐49 years and in the European Union (EU) in 2012 for healthy children aged 2‐17 years .…”
Section: Iga Immune Response Upon Influenza Vaccinationmentioning
confidence: 99%
“…39 They have been used in adults since the 1950s, and from 1987 onwards, the use of Russian LAIV for the prophylaxis of influenza has been widely extended to all age groups including children aged over 3 years. 40 Fluenz R in the EU. 42 Studies performed in mice have demonstrated the predominant protective role played by sIgA, 43,44 even in case of absence of T cells.…”
Section: G a Immune Re S P On S E Up On Influenz A Vaccinationmentioning
confidence: 99%
“… Milestones in the history of influenza vaccines [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. IIV, inactivated influenza vaccine; WHO, World Health Organization; LAIV, live attenuated influenza vaccine.…”
Section: Figurementioning
confidence: 99%
“…33 LAIV has been highlighted as a particularly valuable technology given that the straightforward, high-yield manufacturing process and needle-free administration are more transferable to low-and middle-income countries and advantageous for pandemic surge production. 34 There are very few studies of LAIV in such populations but two recent RCTs assessed efficacy of "Leningrad" LAIV in Senegal 35 and Bangladesh 36 . Surprisingly, the results from these two studies are very different, with no efficacy demonstrated in Senegal, but 41% efficacy in Bangladesh ( Table 2).…”
Section: Introductionmentioning
confidence: 99%